Generalised Ulam-Hyers stability of a n-dimensional additive functional equation in two different methods. (20th March 2020) - Arunkumar, M.; Agilan, P.; Ramamoorthy, S.; Kumar, N. Mahesh
In this paper, the authors investigate the general solution and generalised Ulam-Hyers stability of a n -dimensional additive functional equation in Banach spaces by applying direct and fixed point methods.